The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13550-018-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rifampicin-inhibitable transport on the liver distribution and tissue kinetics of erlotinib assessed with PET imaging in rats

Abstract: BackgroundErlotinib is an epidermal growth factor receptor (EGFR)-targeting tyrosine kinase inhibitor approved for treatment of non-small cell lung cancer. The wide inter-individual pharmacokinetic (PK) variability of erlotinib may impact treatment outcome and/or toxicity. Recent in vivo studies reported a nonlinear uptake transport of erlotinib into the liver, suggesting carrier-mediated system(s) to mediate its hepatobiliary clearance. Erlotinib has been identified in vitro as a substrate of organic anion-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…RIF (40 mg/kg intravenously, i.v.) was injected immediately before [ 99m Tc]mebrofenin as previously described [ 33 ]. The PK of subcutaneously (s.c.) injected DTZ (20 mg/kg) has been reported in rats with plasma concentration > 10 µg/mL (25 µM) obtained 60 min after injection [ 34 ], consistent with the potency of DTZ to inhibit MRP2, assessed in vitro in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RIF (40 mg/kg intravenously, i.v.) was injected immediately before [ 99m Tc]mebrofenin as previously described [ 33 ]. The PK of subcutaneously (s.c.) injected DTZ (20 mg/kg) has been reported in rats with plasma concentration > 10 µg/mL (25 µM) obtained 60 min after injection [ 34 ], consistent with the potency of DTZ to inhibit MRP2, assessed in vitro in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The uptake clearance of [ 99m Tc]mebrofenin from blood to the liver (CL uptake ) was estimated using the integration plot method [ 33 , 35 ] from 0 to 3 min (linear part) after [ 99m Tc]mebrofenin injection using the following equation: . X liver,t represents the total amount of [ 99m Tc]mebrofenin in the liver at the time t, C blood,t represents the concentration of [ 99m Tc]mebrofenin in the blood at time t (derived from the heart ROI).…”
Section: Methodsmentioning
confidence: 99%
“…In mice and rats, rifampicin caused a pronounced reduction in the rate constant for the uptake of [ 11 C]erlotinib from the blood into the liver, while a similar, but markedly less pronounced decrease was observed in humans. These results indicated that rifampicin-inhibitable transporters, possibly OATP2B1 (SLCO2B1), contributed to the distribution of [ 11 C] erlotinib from the blood into the liver [97,98].…”
Section: Pet To Assess Transporter-mediated Ddismentioning
confidence: 97%
“…Several studies have addressed these questions by employing PET with radiolabeled drugs. Already marketed drugs, such as metformin, telmisartan, rosuvastatin, glyburide or erlotinib, have been studied with PET to assess their interactions with hepatocyte transporters and/or their vulnerability to transporter-mediated DDIs, in combination with prototypical transporter inhibitors [37,56,66,70,77,78,94,97,98]. This approach may potentially also find application in the study of new drug candidates to obtain crucial information on tissue distribution and transportermediated clearance, which may ultimately improve drug safety and efficacy.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Two control animals and two elacridar-treated animals were injected with 11 C-erlotinib. Arterial plasma sampling, sample preparation and analytical methods used for the determination of parent 11 C-erlotinib in plasma were performed as previously described [44]. Time activity curves (TACs) of unmetabolized parent 11 C-erlotinib in plasma were expressed as the percentage of injected dose per volume (%ID.mL −3 ) versus time.…”
Section: Impact Of Elacridar On 11 C-erlotinib Plasma Kineticsmentioning
confidence: 99%